Spatial and temporal regulation of homogeneous nucleation and crystal growth for high-flux electrochemical water softening. (1st April 2023) - Kang, Wenda; Li, Lujie; Yan, Liming; Mao, Wei; Wang, Xueqing; Yu, Hongtao; Ma, Chuanjun
Highlights: A sandwich structure module of mesh anode/nylon nets/mesh cathode was first proposed for electrochemical softening. The sandwich structure elevated pH value of solution in cathode chamber rapidly. Homogeneous nucleation of CaCO3 was enhanced. Membrane separation was performed once crystal nucleus just grew larger than membrane pore. High-flux electrochemical water softening was achieved. Abstract: Electrochemical softening is an effective technology for the treatment of circulating cooling water, but its hardness removal efficiency is limited because that nucleation and growth of scale crystals depended on cathode surface. In this study, a novel method was proposed to break through this limit via spatiotemporal management of nucleation and growth processes. A cube reactor was divided into cathodic chamber and anodic chamber via installing a sandwich structure module composed of mesh cathode, nylon nets, and mesh anode. Using this continuous-flowing electrochemical reactor, OH ̄ generated by water electrolysis was rapidly pushed away from cathode surface by water flow and hydrogen bubbles movement. As a result, a wide range of strongly alkaline regions was rapidly constructed in cathodic chamber to play a nucleation region, and homogeneous nucleation in liquid phase replaced heterogeneous nucleation on cathodic surface. Furthermore, the growth process of scale crystals in alkaline regions was monitored in situ. It took only 150 s of residence time to grow to 500 nm, which may be easily separated from water by a microfiltration membrane. With this new method, the precipitation rate was 290.8 g/(hˑm 2 ) and corresponding energy consumption was 2.1 kW·h/kg CaCO3, both were superior to those reported values. Therefore, this study developed an efficient electrochemical softening method by spatial and temporal regulation of homogeneous nucleation and crystal growth processes. Graphical abstract: Image, graphical abstract